2008
DOI: 10.1080/01421590802108331
|View full text |Cite
|
Sign up to set email alerts
|

AMEE Guide 32: e-Learning in medical education Part 1: Learning, teaching and assessment

Abstract: In just a few years, e-learning has become part of the mainstream in medical education. While e-learning means many things to many people, at its heart it is concerned with the educational uses of technology. For the purposes of this guide, we consider the many ways that the information revolution has affected and remediated the practice of healthcare teaching and learning. Deploying new technologies usually introduces tensions, and e-learning is no exception. Some wish to use it merely to perform pre-existing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
411
0
38

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 512 publications
(452 citation statements)
references
References 42 publications
3
411
0
38
Order By: Relevance
“…Within the scope of the electronically implemented PBL applications in medical education, there are examples indicating that sharing learning material supporting classical face-to-face PBLs, online discussion platforms following the PBL sessions, clinical reasoning applications in which students are able to participate in at different times individually or in groups and multimedia scenarios, virtual patients are integrated to PBL sessions [4,7,[9][10][11][12][13]. In Dokuz Eylul Faculty of Medicine model, all of the steps in the classical PBL format were electronically actualized by the students in synchronized e-PBL sessions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the scope of the electronically implemented PBL applications in medical education, there are examples indicating that sharing learning material supporting classical face-to-face PBLs, online discussion platforms following the PBL sessions, clinical reasoning applications in which students are able to participate in at different times individually or in groups and multimedia scenarios, virtual patients are integrated to PBL sessions [4,7,[9][10][11][12][13]. In Dokuz Eylul Faculty of Medicine model, all of the steps in the classical PBL format were electronically actualized by the students in synchronized e-PBL sessions.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the use of education technology and electronic learning applications have become increasingly widespread for education and assessment activities, they have also been integrated to PBL sessions, electronic applications increase the interest and motivation of students and promote learning, in this context, in medical education [4][5][6]. Recently, upon the increase in need for tutors in parallel with the increase in number of students, alternative searches have started to ease the educator's load.…”
Section: Introductionmentioning
confidence: 99%
“…Aspects that are discussed are whether the Learning Management System (LMS) selected supports the chosen learning model and pedagogy and if the software is easy to use (Safie, 2009). Ellaway and Masters (2008) and Idachaba and Idachaba (2012) recommended that e-learning is not merely about the content and delivery of teaching, but is a pedagogical approach that aims to be flexible, engaging and learner-centered undertaking. It is the one that promotes interactions collaboration and communication.…”
Section: Technological Requirementsmentioning
confidence: 99%
“…Studies have also reported that E-learning can be used as an active learning strategy which promotes self-directed learning. [2] In today′s era students are more computer literate and the demand for technologybased learning at a time convenient to them has increased. Thus, there is shift of focus from classroom teaching to self-directed online learning environment which allows students to concentrate effort on useful information that they need to know and enhance retention of material.…”
Section: Introductionmentioning
confidence: 99%